PRODUCTION MANAGEMENT OF CRUDE PALM OIL (CASE STUDY AT “X” COMPANY - Baharuddin Baharuddin; Kadek Rantawan; Andi Tenri Fitriyah; Ratri Retno Utami; Nurhayati Nurhayati; Mulono Apriyanto (Jurnal Industri Hasil Perkebunan, 2022)
Factors that influence Crude Palm Oil (CPO) production is the increase in CPO consumption and with the implementation of CPO production process management, it can meet domestic and export demand. The purpose of this study was to determine the application of CPO production process management at “X” Co. This research has been conducted from May to June 2018. The data collection technique was purposive sampling with descriptive analysis. The results obtained indicate that based on the implementation of production management, improvements are still needed through increasing CPO production by increasing the capacity of production machines from 2.5 tons per lorry to 10 tons per lorry. In addition, it is also necessary to improve the quality of human resources and products to increase the company's competitiveness. Keywords: management, production, demand, CPO, planning